Extension of Healthy Life Span of Dialysis Patients in the Era of a 100-Year Life - Inaba, Masaaki; Mori, Katsuhiko (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Malnutrition is becoming a more prominent health problem, with an increasing number of elderly CKD patients being put on dialysis. In addition, the presence of inflammation, sarcopenia/frailty, diabetes, and CVD is a definite and independent risk factor associated with higher mortality in this population. Although the restriction of protein intake has been recommended to protect eGFR decline, hyperphosphatemia, and hyperkalemia in CKD patients, it might accelerate the loss of skeletal muscle and adipose mass, leading to a poor prognosis. Therefore, flexible responses are considered regarding whether protein restriction should be continued or loosened in pre-dialysis CKD patients. In undernourished elderly patients undergoing hemodialysis, sufficient calorie/protein intake is necessary to counteract the development of sarcopenia/frailty. It is expected that the application of new drugs including phosphate binders and potassium chelators may achieve both a high enough intake and balanced levels of phosphate and potassium. Furthermore, the improvement of deficient micronutrients and poor appetite is also necessary. Comprehensive care is essential for the wellbeing of elderly patients undergoing hemodialysis. The topicof this Special Issue is "Extension of Healthy Life Span of Dialysis Patients in the Era of a 100-Year Life".